Uma crítica à realidade e a Deus Um estudo exegético em Jó 24,1-12 - Calonga, Tania Aparecida da Silva (2004)
The Book of Job belongs to the wisdom literature of Israel. Its content represents a great debate among the wise of the era. Those involved in this debate were members of an educated class who knew how to read and write. Wisdom was highly valued and understood as prudent orientation for life. The text 24,1-12 belongs to the poetic section of the book. The poem was written in the first half of the fifth century A.C., in the post-exilic period during the Persian domination. This Empire brought profound changes to the life of the people in Judah. In spice of the apparent tolerance in the part of the government, very effective methods were created to reach their goals. Behind a strong bureaucratic, fiscal and military apparatus they controlled and guaranteed order and the payment of tributes. The temple became na intermediary between the Empire and the people. The economy and society were structured in accordance with the regime imposed by the Persians. Economic and administrative policy favored the enrichment of the dominant class, and consequently the systematic impoverishment of the peasants. The priests were the leaders of the people, and the theology of retribution was strengthened considerably during this period. Nonetheless, the justice of God expressed by the theology of retribution faced the problem of evil and the suffering of the just. Personal experience and the observation of reality generated a movement of resistance to the theology of retribution. In chapter 24, 1-12, Job contemplates a society divided between oppressors and oppressed. He challenges the function of society by showing its weaknesses and contradictions. His intention in the text is to show, via reflections on reality, why he does not agree with the affirmations of the wise that defend the theology of retribution. He does so by demonstrating the infallible punishment of the impious rich, and reflecting on the suffering of the poor as an indication of punishment.(AU)